Sistem Informasi Inventory Barang Jadi Pada PT. Varia Usaha Beton Gresik - Agus Supra Yitno; Emmy Wahyuningtyas; Firman Hadi S.P (Melek IT : Information Technology Journal, 2017)
The website is already been used in many purposes and fields, such as education, public services, health, politic, security, banking and economy, and construction where infrastructure and property are included to industry sector. In the storing finished goods and precast concrete in PT. Varia Usaha Beton Gresik’s warehouse, documenting data of those should be easily conducted in order to checking the availability of stock, to assure the movement of goods, and to supply information of finished goods’ inventory. In addition, PPIC (Production Planning Inventory Control) also requires a long time to report the finished goods’ inventory due to recap the data of incoming goods and outgoing goods stored in the warehouse. Moreover, reporting report from each division is also taking time because the long distance between sections head, warehouse, marketing, PPIC and transportation division.